2018
DOI: 10.1111/aej.12290
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate dentistry students’ perception of difficulties regarding endodontic treatment

Abstract: The present study aimed to identify students' perceptions of endodontic treatment at a Brazilian university through a survey, which analysed student profiles and their difficulties in 2016. One hundred and two students who had experienced endodontic, laboratory or clinical procedures answered a survey based on their experiences, regarding their perceptions, experience and self-confidence levels. Results demonstrated that there was no significant difficulty among students regarding anaesthesia, rubber dam use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 17 publications
(21 reference statements)
4
24
0
10
Order By: Relevance
“…Most problems were experienced by the stutters when the appropriate medication was prescribed during multi-session root canal treatment. Most students, however, confirmed that they were able to overcome the aforementioned difficulties, thanks to further education and experience [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most problems were experienced by the stutters when the appropriate medication was prescribed during multi-session root canal treatment. Most students, however, confirmed that they were able to overcome the aforementioned difficulties, thanks to further education and experience [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, according to the results of this study, other technological resources are utilised during the training in endodontics. There is scientific evidence that the use of these resources has numerous advantages for dental students and professionals, reducing working time and increasing predictability of results 42,43 . It is known that programme quality is related not only to curriculum planning but also to investment in infrastructure and equipment by institutions 44…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical endodontic training is essential to prepare under-and postgraduate dental students in the performance of adequate and predictable root canal treatments before the transition to a clinical setting (1)(2)(3). Various studies have indicated that European populations continue to receive unsatisfactory standard root canal (3,4).…”
Section: Introductionmentioning
confidence: 99%